ARTIFICIAL INTELLIGENCES DEPLOYMENT IN TERTIARY EDUCATION - Olowonefa , Jethro Abiodun (Multi-Disciplinary Research and Development Journals Int’l, 2025)
Artificial Intelligence (AI) is transforming global higher education by reshaping teaching, research, and community engagement. This chapter explores the deployment of AI in tertiary institutions with specific emphasis on the Nigerian context. It clarifies key concepts, outlines the imperative of integrating AI into higher education, and discusses its applications in teaching, research, and community service. AI technologies such as Intelligent Tutoring Systems, automated grading, plagiarism detection, predictive analytics, and adaptive learning platforms enhance teaching and learning by supporting personalized instruction, improving efficiency, and promoting academic integrity. In research, AI facilitates advanced data analytics, literature reviews, recommendation systems, and collaboration, accelerating knowledge creation and innovation. Community service initiatives also benefit from AI through improved needs assessment, resource allocation, and data-driven planning. Furthermore, the integration of AI and machine learning (ML) into academic curricula equips students with computational thinking, multidisciplinary perspectives, and lifelong learning skills, thereby enhancing employability and preparing them for the demands of the Fourth Industrial Revolution. Despite challenges such as infrastructure deficits, policy gaps, and ethical concerns, AI offers significant opportunities for Nigerian tertiary education to align with global technological advancements. The chapter concludes that strategic integration of AI can enrich educational quality, strengthen research productivity, and advance community impact in Nigerian universities, positioning them as competitive actors in the global knowledge economy.